Human population history and evolution of culture: A phylogenetic approach - Duda, Pavel (Jihočeská univerzita, 2017)
This thesis uses phylogenetic and phylogenetic comparative methods to investigate human population history and evolution of cross-cultural variation. Such research requires a robust phylogenetic hypothesis of human populations as a framework. This thesis uses a supertree approach to infer a composite phylogeny of human populations based on published phylogenetic trees based on genetic and linguistic data. It assesses the stability of the inferred supertree topology and identifies individual populations whose phylogenetic position is particularly unstable. It assesses the congruence between genetic and linguistic data and tests hypothesis about language relationships and coevolution between genes and languages on a global scale. The supertree is used to reconstruct the origin and evolution of religious beliefs and behaviors using a global sample of hunter-gatherer populations and a set of phylogenetic comparative methods. This thesis also describes evolution of Central African pygmies, a group of human populations that represents an interesting case of morphological and cultural adaptation in human species, and reviews the history and current developments of phylogenetic (tree building) approaches to cross-cultural variation.
Human population history and evolution of culture: A phylogenetic approach